FAKTOR RISIKO YANG MEMENGARUHI KEJADIAN MUSCULOSKELETAL DISORDERS (MSDs) PADA DOKTER GIGI : LITERATURE REVIEW - Faikha Dhista Rahmaningrum; Baju Widjasena; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Dentists in carrying out their work must be full of concentration so that it is not uncommon for them to do work with awkward postures for the comfort and safety of patients. Musculoskeletal disorder is a disorder that can be felt by many people because its occurrence is widespread and is a common cause of impaired function and decreased quality of life. Objective: To analyze the risk factors that influence the incidence of musculoskeletal disorders (MSDs) in dentists based on literature in the form of articles and national and or international accredited journals that have been published. Method: Descriptive type with a qualitative approach. The research method used is the literature review method or a method that is systematic by identifying and reviewing the results of existing research to solve cases in accordance with the variables that have been determined in the study. The results of the study related to the factors that influence the risk of MSD occurrence in dentists, namely individual factors including age, gender, years of service and work factors including work posture, workload, duration of work, and repetition. The factor of tenure on the risk of MSD is the factor that has the most reviews in several articles than other individual factors. So, the factors of work posture and work duration are the factors that have the most reviews on the articles used than other work factors.